HIV Care Experiences During the COVID‑19 Pandemic: Mixed‑Methods Telephone Interviews with Clinic‑Enrolled HIV‑Infected Adults in Uganda - Linnemayr, Sebastian; Mayo‑Wilson, Larissa Jennings; Saya, Uzaib; Wagner, Zachary; MacCarthy, Sarah; Walukaga, Stewart; Nakubulwa, Susan; Karamagi, Yvonne (AIDS and Behavior, 2021)
COVID-19 measures that restrict movement may negatively impact access to HIV care and treatment. To contribute to the currently limited evidence, we used telephone interviews with quantitative and qualitative questions to examine how clients perceived COVID-19 and its effect on their HIV care and ART adherence. One hundred (n = 100) Ugandan adults on ART from an existing study were randomly selected and enrolled. Interviews were recorded, transcribed, and analyzed using descriptive statistics and rapid content analyses. 76% of clients indicated that COVID-19 negatively impacted travel to HIV clinics; 54% perceived that coming to the clinic increased their risk of acquiring COVID-19; and 14% said that COVID-19 had negatively impacted their ART adherence. Qualitative feedback suggests that fear of COVID-19 infection discouraged clinic attendance while stay-at-home orders helped routinize ART adherence and employ new community-based approaches for HIV care. Addressing negative unintended consequences of COVID-19 lockdowns on HIV care is urgently needed.
Keywords: Adherence; Uganda; Antiretroviral treatment; ART; COVID-19; Pandemic; Mixed methods; Mobile phone; Survey